FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN WASTING PADA BALITA USIA 6-59 BULAN - Arifin, Hasriany; Lestaluhu, Santi Aprilian; Alfiah, Alfiah; Sada, Merinta (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Wasting is one of the global health issues that has a widespread impact across nearly all regions of the world, both in developing and developed countries. Wasting is a nutritional problem that occurs in infants aged 0–59 months. The objective of this study was to identify the factors associated with wasting in infants aged 6–59 months. The study design used in this research was a case-control study. The study was conducted in the service area of the Susunan Baru Health Center in June 2024. The population consisted of all children aged 6–59 months classified as wasting and non-wasting. The sample size was 88 participants, comprising 44 cases and 44 controls. The sampling technique used was total sampling. The research instrument used a questionnaire. Data analysis was performed using univariate and bivariate methods. The results of the study showed a relationship between a history of low birth weight (p-value: 0.042) and a history of exclusive breastfeeding (p-value: 0.039) and the occurrence of wasting. It is recommended that mothers with toddlers actively participate in child health programs such as posyandu and nutrition counseling, and regularly take their toddlers to health facilities for check-ups.Keywords: Exclusive Breastfeeding, Toddlers, Wasting.